1988
DOI: 10.1159/000125004
|View full text |Cite
|
Sign up to set email alerts
|

Human Recombinant Interleukin-1Beta and -Alpha, but Not Recombinant Tumor Necrosis Factor Alpha Stimulate ACTH Release from Rat Anterior Pituitary Cells in vitro in a Prostaglandin E<sub>2</sub> and cAMP Independent Manner

Abstract: The pituitary-adrenal axis is known to be stimulated during the acute-phase response. As cytokines play a central role in mediating the constellation of host response occurring during the acute-phase response it was of interest to assess the ability of cytokines to stimulate ACTH secretion from normal pituitary cells in culture. We used human recombinant interleukin-1β and -α (hrlL1β, hrlL1α) and human recombinant tumor necrosis factor α (hrTNFα) to analyze the ability of these cytokines to induce ACTH secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
1
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(42 citation statements)
references
References 25 publications
6
34
1
1
Order By: Relevance
“…This could also indicate that taken together, CRF,, and AVP account for all CRF, measured in our extracts, but definite evidence would require the comparison of this CRF, with that of standard solutions of CRF,, and AVP. Therefore, our results neither rule out the possibility that other known ACTH secretagogues such as Interleukin 1p (22,23), angiotensin 11 (24) and catecholamines (25) contribute to this biological activity, nor the fact that these other ACTH secretagogues may act in vivo within the hypothalamus to release CRF,, (26)(27)(28). To assess the effect of chronic administration of glucocorticoids on the levels of CRF,, and AVP we compared the hypothalamic contents of these two factors in patients who had received corticosteroids with those of control patients free of chronic corticosteroid administration.…”
Section: Discussioncontrasting
confidence: 70%
“…This could also indicate that taken together, CRF,, and AVP account for all CRF, measured in our extracts, but definite evidence would require the comparison of this CRF, with that of standard solutions of CRF,, and AVP. Therefore, our results neither rule out the possibility that other known ACTH secretagogues such as Interleukin 1p (22,23), angiotensin 11 (24) and catecholamines (25) contribute to this biological activity, nor the fact that these other ACTH secretagogues may act in vivo within the hypothalamus to release CRF,, (26)(27)(28). To assess the effect of chronic administration of glucocorticoids on the levels of CRF,, and AVP we compared the hypothalamic contents of these two factors in patients who had received corticosteroids with those of control patients free of chronic corticosteroid administration.…”
Section: Discussioncontrasting
confidence: 70%
“…Another group was pretreated by first injecting ahCRF earlier observation [84]. Beginning with the original demonstration of IL-1-induced ACTH release from a corticotroph cell line [3], AtT20, and subsequent confirmations and demonstrations of this response with primary pituitary cell cultures [85][86][87][88][89][90], a controversy ensued as to whether in vivo IL-1-mediated ACTH increases originated at the level of the hypothalamus or pituitary gland [91]. Although the consensus of studies concluded that ACTH release occurs as a result of IL-1 eliciting hypothalamic CRH release and that the CRH is entirely responsible for pituitary ACTH secretion [92][93][94][95], these findings were difficult to reconcile with the abundance of IL-1 receptors in the pituitary gland when compared with the hypothalamus [96,97].…”
Section: Future Directions For the Sixth Sensementioning
confidence: 99%
“…Growth hormone (GH), prolactin (PRL), luteinizing hormone (LH), and follicle-stimulating hormone (FSH) secretion by rat pituitary cells have been reported not to be influenced by IL-1· [9], whereas other reports have shown stimulation of GH, LH and thyroidstimulating hormone (TSH) secretion [10], together with inhibition of PRL release [11,12]. In rat pituitary cell cultures, ACTH secretion was stimulated [7,9,10,[12][13][14] or not influenced [15,16] by IL-1ß, whereas secretion of this pituitary hormone is enhanced by IL-1· in AtT20 cells [17][18][19][20] and in human corticotroph pituitary adenoma cell cultures [17]. Lastly, IL-1 further increases ACTH secretion by corticotrophs previously exposed to CRH [21].…”
Section: Cytokines and Thymic Hormones Modulate Hypothalamic-pituitarmentioning
confidence: 99%